Kinematics Analysis and Scale Synthesis of a Novel Spherical Parallel Mechanism - Zhen Chang; Chengbo Wang; Gaofeng Wang; Jianshe Gao (Jixie chuandong)
In order to solve problems of high coupling degree，inconvenient control and insufficient flexibility when spherical parallel mechanism is applied in the field of robot bionics，a novel three-branch spherical parallel mechanism with semi-decoupled characteristics is proposed. Based on the screw theory，the degree of freedom （DOF） of the mechanism is analyzed. The forward and inverse kinematics solutions of the mechanism are solved by the vector method and the decoupling characteristics of the mechanism are analyzed. The mechanism has a 3-DOF to rotate around the X axis，Y axis，Z axis，and the rotation around the Z axis is controlled by only one branch，while the other two branches jointly control the mechanism to move around the X axis，Y axis. Jacobian matrix is obtained based on differential transformation method and singular configuration is discussed. The workspace of the mechanism is determined by the boundary search method with singular configuration and bar interference as constraints. Based on the decoupling characteristics of the mechanism，a global mean dexterity with decoupling coefficient is proposed. Taking the workspace and global mean dexterity as the optimization goals，the particle swarm optimization algorithm （PSO） is used to synthesize the structure parameters of the mechanism. After the optimization，the workspace is enlarged and the motion performance in this space is good，which provides a theoretical basis for the prototype design of the spherical parallel mechanism and the scale synthesis of other semi-decoupling mechanisms.